Perceiving speed—The color can matter. Issue 6 (14th September 2019) - Mentzel, Stijn V.; Schücker, Linda; Hagemann, Norbert; Strauss, Bernd
Abstract: This study focuses on examining color effects of perceived speed in an individual noncompetitive sport context, treadmill running. In addition, the presence of individual trends for color effects are inspected by observing the connection of color effects in a sport‐specific video rating task with those found in an individual color association task. For this, 32 participants rated the perceived running speed of 48 videos depicting runners on a treadmill at seven different speed settings. Furthermore, participants rated a range of additional sport‐specific performance parameters. The runners in the video were shown wearing either a red, blue, or gray jersey, gray being used to strengthen the cover story. As a secondary task, the participants performed a modified Stroop task to assess implicit color associations. The results showed a significant color effect for speed; runners depicted in red were perceived as running at higher speeds compared to blue. No significant color effects were found for the other sport‐specific parameters. Finally, there was no significant covariate effect of the modified Stroop task for the speed perception color effect. These findings indicate that, in situations in which speed must be judged, red might be perceived as going faster.